Investigation of non-precious metals for the development of low cost catalytic converter - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur (2011)
This paper discusses the uses of non-precious metals in catalytic converters to bring down the cost without sacrificing the performance capability. Copper powder and nickel catalyst were chosen as the alternative catalysts to reduce the use of precious group metals (PGMs) platinum, palladium, and rhodium. Simulation by COMSOL has shown that Nickel and copper were very effective in reducing NOx during rich condition of air-fuel mixture while oxidizing CO and HC during lean condition. Simulations using FLUENT and COMSOL have shown the actual characteristics of the catalytic converter performance. The flow throughout catalytic converter and the backpressure have successfully determined. Furthermore, catalyst conversion efficiency also has been shown clearly. On the other hands, the experimental results have excellently validated the simulation results in terms of the nature and trends of the catalytic converter performance as well as its efficiency. Catalyst distribution and application of the non-zoning monolith substrates have further contributes to cut down the production cost. It was found that the low cost catalytic converter was able to meet the EURO 2 emission regulation control and has optimum backpressure at full throttle.